Writing with attitude: Stance expression in learner and professional dentistry research reports. (April 2017) - Crosthwaite, Peter; Cheung, Lisa; Jiang, Feng (Kevin)
Abstract: Medical students often lack key skills in academic writing, yet good academic writing is often a pre-requisite for employment, promotion and enculturation into the profession. This article focuses on the rhetorical strategies used for the presentation of academic stance by student writers of dentistry research reports. Adopting a contrastive, corpus-based approach, we compare student writing with that of comparable professionally-written research reports for evidence of hedging, boosting, self-mention and attitude markers. Our findings indicate that professional reports exhibit a narrower set of linguistic devices than used by student writers, who tend to use a much wider range of the four stance feature types analysed for discussion of both others' and their own personal stance, both across whole texts and by section. We discuss pedagogical implications for ESP professionals working to more closely align student writing with that of professional norms. Highlights: We analysed stance features of dentistry research reports by novice undergraduate writers vs. those of professional writers. Novice writers use a wide range of hedges, boosters, self-mention and attitude markers when writing, and use them frequently. Professional writers generally use a smaller range of stance features than novice writers, and use them less frequently. Teachers may consider raising awareness of these differences for English-in-the-discipline content.